Students’ Understanding on Teacher’s Speech Acts in the Classroom Instructions - Zahroh, Nur Fatimahtus; Susanto, Fajar (JET ADI BUANA, 2022)
This study analyzes the teacher's speech acts in the classroom. This study covers two points of discussion: speech acts in the teacher’s instructions and the students’ understanding to the instructions as speech acts. To describe two problems of this study, a qualitative descriptive research was applied in which the transcription of the conversation between the teacher and students can describe how the speech acts uttered by the teacher can be understood by the students. The results of this study indicated that explicit and implicit speech acts that were frequently uttered by the teacher in giving instructions in the learning process in which those instructions can be found in opening, core, and closing. Explicit and implicit speech acts can be categorized as directive form, namely command and/or request. Those utterances are used by the teacher to tell students to do something. Besides that, the students could understand the teacher's instructions in the classroom in various ways such as taking action, and giving statements, but there were some instructions that were not given a response by students.